Synthesis and Nuclear Magnetic Resonance Studies of the Tetrakis (Tri-Para-Tolyl Phosphite) Nickel (0) Hydride System - Moffat, Karen Ann (My University, 1984)
This thesis is primarily concerned with an investigation of the reaction of tetrakis(tri-p-tolyl phosphite)nickel(0) with strong acids, using 1H, 31P and 2H NMR. The results differ from those previously obtained for similar reactions with other Ni(0) phosphites, in that both five and four-coordinate nickel hydrides are formed in concentrations sufficient for spectroscopic studies. The four-coordinated hydride is believed to be the catalytically active species in a number of reactions catalyzed by Ni(0) phosphites. Variable-temperature studies show that the four-coordinate hydride complex is a fluxional molecule. The exchange process is exclusively intramolecular in nature.
A very simple method was used to analyze the NMR data and obtain activation parameters for the exchange process. These parameters were compared with those reported in the literature for related intramolecular and intermolecular reactions. The large negative entropy of activation is interpreted in terms of ion pairing in the transition state. NMR evidence for the structure of the products resulting from the reactions of acids with both the metal complexes and the free phosphite ligands is presented. The conditions necessary for the observation of four-coordinated nickel hydrides are also discussed.
Keywords: synthesis, nuclear, magnetic, resonance, phosphite, nickel, hydride, system, acids, reactions, species, fluxional, molecule, ligands